HAJI DAN INOVASI: INVESTIGASI PROSES INOVASI PELAYANAN HAJI DALAM NEGERI - Atmadja, Ferry Setyadi (Jurnal Manajemen Dakwah, 2023)
This view of innovation is a potential basis for meeting the needs of today's society. Observing the success of realizing innovation in the Hajj services sector can certainly be a breath of fresh air in facing the challenges of globalization and answering the classic pathologies of organizing the Hajj. One of them is the Yogyakarta City Ministry of Religion Office which has proven that the presence of innovative Hajj services has become a benchmark for other organizations. Based on this, this research seeks to investigate how the innovation process carried out as an integral part of realizing Hajj service innovation can be said to be successful. This study uses a qualitative research approach with strategic case studies to empirically reveal experiences in the field. The results of this research show that innovation in the Hajj Service PTSP program does not occur incidentally but can be traced into a framework for realizing innovation through the initiation, implementation and diffusion stages. The third stage in the Hajj Service PTSP innovation process should follow a simple linear model where these stages have their own actions that run progressively.